2017
DOI: 10.1007/s00246-017-1785-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D Echocardiogram-Derived 3D Printed Valve Models to Molded Models for Simulated Repair of Pediatric Atrioventricular Valves

Abstract: Mastering the technical skills required to perform pediatric cardiac valve surgery is challenging in part due to limited opportunity for practice. Transformation of 3D echocardiographic (echo) images of congenitally abnormal heart valves to realistic physical models could allow patient-specific simulation of surgical valve repair. We compared materials, processes, and costs for 3D printing and molding of patient-specific models for visualization and surgical simulation of congenitally abnormal heart valves. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…Promising results have been achieved both in combining 3D echo with CT or as isolated datasets. [20][21][22] However, a recent study states that CT may be better than echocardiography when the left atrial appendage is the region of interest, to plan device closure in patients with atrial fibrillation. 23 As this field is still developing, new imaging modalities are emerging as possible options for 3D printing.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Promising results have been achieved both in combining 3D echo with CT or as isolated datasets. [20][21][22] However, a recent study states that CT may be better than echocardiography when the left atrial appendage is the region of interest, to plan device closure in patients with atrial fibrillation. 23 As this field is still developing, new imaging modalities are emerging as possible options for 3D printing.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…3 Functional 3D models and their coupling with a mock circulatory system. Images in the figure are from the literature [72][73][74] same two materials to create aortic valve complexes, and confirmed their feasibility for ultrasound imaging. Biglino et al [72] made a blood vessel model using TangoPlus, and demonstrated its suitability for fabricating arteries, although its mechanical properties might not be suitable for modeling softer blood vessels.…”
Section: Flexible Materials For 3d Cardiovascular Modelsmentioning
confidence: 57%
“…Using a rigid 3D model as a mold, a flexible model can alternatively be obtained by painting it with silicone (such as smooth-on, Echoflex). Scanlan et al [73] compared 3D models of the tricuspid valve obtained by the two methods, and reported that both closely replicated the patient's anatomy, while the silicone model was better at simulating the texture of cutting and stitching. Based on the ultrasound images, a mitral valve prolapse model created by Olivia et al [74] using Echoflex 00-30 also had good fidelity to the preoperative three-dimensional echocardiogram.…”
Section: Flexible Materials For 3d Cardiovascular Modelsmentioning
confidence: 99%
“…The echocardiographic data were analyzed with opensource software for volumetric data navigation 3D Slicer [21] and SlicerHeart extension [22] to navigate and slice the volume with three orthogonal views. Each dataset was navigated to obtain the following views: (i) short axis MV view ( Fig.…”
Section: Pathological Model Assessmentmentioning
confidence: 99%